Responsible lobbying : conceptual foundations and empirical findings in the EU - Bauer, Theresa (Springer Gabler, 2017)
This study investigates the awareness and practice of responsible lobbying in the EU and analyzes benefits and antecedents. A multidimensional model of responsible lobbying is developed which provides normative guidelines and allows for determining the degree of responsible lobbying in practice. The empirical part analyzes responsible lobbying in the EU by combining a quantitative analysis based on a survey among 142 lobbyists with a qualitative examination based on interviews. The analysis reveals that criteria of responsible lobbying are fulfilled to a large extent according to the lobbyists. This study comes at a time when researchers and practitioners increasingly recognize the need to establish responsible lobbying by aligning Corporate Social Responsibility (CSR) and lobbying. Contents " Literature on CSR, lobbying and responsible lobbying " A multidimensional model of responsible lobbying " Analysis of benefits and antecedents of responsible lobbying " Empirical insights from a survey and interviews with lobbyists Target Groups " Researchers and students in the area of CSR/business ethics, lobbying/public affairs, management " Managers and consultants The Author Dr. Theresa Bauer is professor of international management and marketing at SRH FernHochschule Riedlingen, Germany. She received her PhD from Humboldt-University Berlin, Germany. She has work experience as a lecturer at Raffles University Iskandar, Malaysia, and as a public relations manager in various European companies and institutions.
Keywords: Lobbying -- European Union countries.; Leadership -- European Union countries.; European Union countries.; elektronické knihy; electronic books